Educational Thought of Ikhwan al-Safa - Hamimah, Nur; Sihotang, Jahrul; Hanum, Azizah (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study explores the educational thought of the Ikhwan al-Safa a significant group of thinkers in Islamic intellectual history. Known for their comprehensive approach to knowledge and education, the Ikhwan al-Safa produced influential philosophical and educational treatises during the Islamic Golden Age. This research focuses on analyzing their writings to uncover their foundational principles regarding education. Key themes include the integration of various branches of knowledge, the cultivation of moral virtues, and the pursuit of wisdom as a holistic educational goal. The study employs a qualitative approach with content analysis, examining primary texts attributed to the Ikhwan al-Safa to elucidate their educational philosophy. The findings aim to provide insights into how their educational ideas resonate with contemporary educational challenges and contribute to discussions on holistic education in the modern context.